Survey on the Use of Laminated Bamboo Panel in Malaysia - Muhammad Syahmi Shaiful Mu’azzam; Siti Juita Minoor Shaharizal; Nur Alia Najiihah Azman; Salman Salim (Multidisciplinary Applied Research and Innovation, 2022)
Bamboo is known as the grass that is the fastest growing plant in the world. It is officially able to be one of the main materials in a building construction because of its advantages which have strong properties, durable, environmentally friendly and easily available compared to wood. There are many advantages of bamboo that are still hidden and not disclosed to the public in Malaysia which makes more difficult for the bamboo industry to achieve a high level of development. But nowadays, society are not exposed to the benefits of bamboo compared to wood. There are several industries and companies in Malaysia produce bamboo-based products. Many unique bamboo-based products have been successfully produced. The questionnaire was distributed to respondents which is engagement in the bamboo industry sector. The awareness of using the laminated bamboo panel in community was measured. There are several problems of using laminated bamboo panel was analyzed and some recommendations to improve the common problems of using the laminated bamboo panel.